Design and implementation of digital filters with very high frequency response flexibility for multi-standard wireless communication receivers - Dhabu, Sumedh Somnath (2016)
Variable digital filters and reconfigurable filter banks (the filters and filter banks whose frequency response can be changed on-the-fly, based on the desired specifications) find application in multi-standard wireless communication receivers for channelization and spectrum sensing. Realization of area- and power-efficient, dynamically reconfigurable digital filters and filter banks is a challenging task. This thesis proposes area-efficient variable digital filters and reconfigurable filter bank architecture suitable for multi-standard wireless communication receivers. Proposed reconfigurable architectures offer different trade-offs between filter complexity and frequency response flexibility.